2018
DOI: 10.4103/jomfp.jomfp_143_18
|View full text |Cite
|
Sign up to set email alerts
|

Study of salivary arecoline in areca nut chewers

Abstract: Aims: Arecoline, a predominant alkaloid present in arecanut, has been implicated in the pathogenesis of several oral diseases because of its mutagenic and carcinogenic potential. The response of cultured cells to arecoline is highly dependent on its concentration; arecoline stimulates cultured cells above 0.1 μg/ml and is cytotoxic above 10 μg/ ml. Although this alkaloid seems important for areca nut induced oral diseases and carcinogenesis, little is known of the levels achieved before, during an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
4
8
0
Order By: Relevance
“…IEGs are genes which are activated transiently and rapidly in response to a wide variety of cellular stimuli. These characteristics of Egr-1 are consistent with the wavy change of Arecoline concentration in areca nut chewer's saliva [20]. And in this study, we also produced an Arecoline concentration uctuation by replacing half of the cell culture medium every 24 hours.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…IEGs are genes which are activated transiently and rapidly in response to a wide variety of cellular stimuli. These characteristics of Egr-1 are consistent with the wavy change of Arecoline concentration in areca nut chewer's saliva [20]. And in this study, we also produced an Arecoline concentration uctuation by replacing half of the cell culture medium every 24 hours.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is true that the areca nut chewing increases the risk of oral cancer and oral submucous brosis. In fact, the salivary Arecoline level during chewing were about 0.1 µg/ml, and increased to about 0.3 µg/ml after chewing [20], which is much lower than the concentration used in most experiments.…”
Section: Low Dose Arecoline Induces the Proliferation Of Broblastsmentioning
confidence: 68%
See 1 more Smart Citation
“…Chewing areca nuts is known to increase the risk of oral cancer and OSF. The level of arecoline present in the saliva during areca nut chewing has been found to be around 0.1 μg/ml, and has been found to increase to about 0.3 μg/ml after chewing [ 24 ]; these concentrations are much lower than the concentration of arecoline used in most experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al found that arecoline was cytotoxic to human oral fibroblasts at concentrations greater 50 μg/ml due to depletion of intracellular thiols and inhibition of mitochondrial activity [ 12 , 30 ]; Jeng et al found that arecoline treatment inhibited the migration, attachment, spreading, growth, and collagen synthesis of human oral fibroblasts at concentrations of 0.4 mM (62 μg/ml) and 1 mM (155 μg/ml) [ 11 ]. Venkatesh et al found that arecoline levels in the saliva were about 0.1 μg/ml to about 0.3 μg/ml after chewing commercially available areca nuts [ 24 ], which is much lower than the concentration of arecoline used in most experiments. In this study, we found that low doses of arecoline could promote the proliferation of human oral fibroblasts.…”
Section: Discussionmentioning
confidence: 99%